Spiritualitas Seorang Gembala Melalui Bentuk Komunikasi terhadap Jemaat: Sebuah Analisis Kolose 3:5-17 - Anwar Three Millenium Waruwu; Ampinia Rahap Wanyi Rohy (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
This article discusses the spirituality of a pastor in communicating with his congregation, using Colossians 3:5-17 as a guide. The research method used is literature review with a descriptive approach. The purpose of this study is to understand how a pastor can develop his spirituality in guiding and communicating with his congregation. The results of the study show that the spirituality of a pastor is crucial in forming effective communication with his congregation. In the analysis of Colossians 3:5-17, it is found that a pastor must have a character that is in line with the teachings of Christ and must develop good communication skills to provide proper guidance to his congregation.